Common functional polymorphism within miR-146a and miR-196a-2 as susceptibility loci for hepatocellular carcinoma: An updated meta-analysis - Chen, Ming (Meta Gene, 2015)
BACKGROUND: Mutations or single nucleotide polymorphisms (SNPs) within the gene region of microRNAs play an important role for the development of hepatocellular carcinoma (HCC). Extensive studies have tried to investigate the susceptibility role of miR-146a rs2819164 and miR-196a-2 rs11614913. However, these results are still inconsistent and inconclusive. We undertook a meta-analysis containing primarily Asian studies to assess the associations of the two SNPs with HCC risk. METHODS: 19 studies including miR-146a (7170 cases and 9443 controls) and 15 studies including miR-196a-2 (6417 cases and 7627 controls) were used for meta-analysis. Odds ratios and 95% CI were calculated to assess the association in five different genetic models. RESULTS: For the rs2910164 polymorphism of miR-146a, significantly increased risks for HCC were observed when all studies were pooled under two models (CG vs CC: OR = 1.11, 95% CI = 1.02–1.21, P = 0.021; GG + CG vs CC: OR = 1.11, 95% CI = 1.01–1.22, P = 0.035). For the rs11614913 polymorphism of miR-196a-2, significant increased risks for HCC development were observed when all studies were pooled under four models (C vs T: OR = 1.14, 95% CI = 1.06–1.23, P = 0.001; CC vs TT: OR = 1.31, 95% CI = 1.12–1.53, P = 0.001; CC + TC vs TT: OR = 1.16, 95% CI = 1.03–1.31, P = 0.018; CC vs TC + TT: OR = 1.14, 95% CI = 1.00–1.30, P = 0.043). CONCLUSION: Our results show that the two common SNPs within the miRNAs were associated with modest increased risk of HCC (OR < 1.6), especially in the Asian population. Larger population-based studies validating these results are needed.